Automated computer-aided stenosis detection at coronary CT angiography: initial experience. - Arnoldi E; Gebregziabher M; Schoepf UJ; Goldenberg R; Ramos-Duran L; Zwerner PL; Nikolaou K; Reiser MF; Costello P; Thilo C; Arnoldi, Elisabeth; Gebregziabher, Mulugeta; et al. (European Radiology, 2010)
Objective: To evaluate the performance of a computer-aided algorithm for automated stenosis detection at coronary CT angiography (cCTA).Methods: We investigated 59 patients (38 men, mean age 58 +/- 12 years) who underwent cCTA and quantitative coronary angiography (QCA). All cCTA data sets were analyzed using a software algorithm for automated, without human interaction, detection of coronary artery stenosis. The performance of the algorithm for detection of stenosis of 50% or more was compared with QCA.Results: QCA revealed a total of 38 stenoses of 50% or more of which the algorithm correctly identified 28 (74%). Overall, the automated detection algorithm had 74%/100% sensitivity, 83%/65% specificity, 46%/58% positive predictive value, and 94%/100% negative predictive value for diagnosing stenosis of 50% or more on per-vessel/per-patient analysis, respectively. There were 33 false positive detection marks (average 0.56/patient), of which 19 were associated with stenotic lesions of less than 50% on QCA and 14 were not associated with an atherosclerotic surrogate.Conclusion: Compared with QCA, the automated detection algorithm evaluated has relatively high accuracy for diagnosing significant coronary artery stenosis at cCTA. If used as a second reader, the high negative predictive value may further enhance the confidence of excluding significant stenosis based on a normal or near-normal cCTA study.